The Application of 3D-Printing and Nanotechnology for the Targeted Treatment of Osteosarcoma - Suleman, Ayesha; Kondiah, Pierre P. D.; Mabrouk, Mostafa; Choonara, Yahya E. (Frontiers in Materials, 2021)
Osteosarcoma is a malignant bone neoplasm prevalent in adolescents. Current therapies include chemotherapy and surgery. Surgical resection of osteosarcoma induces a large bone defect which may be overcome by employing scaffolds for bone tissue engineering. This review details the polymers and bioceramics that may be used to fabricate 3D printed scaffolds for bone regeneration and the nanotechnology strategies that may be incorporated into such scaffolds. Natural polymers discussed include chitosan, alginate, collagen, gelatin, and silk fibroin. Synthetic polymers discussed include polycaprolactone, polyurethane, poly(lactic)acid and poly(vinyl) alcohol. Bioceramics that are utilized in bone regeneration such as calcium phosphate, calcium silicate and bioglasss are elaborated on. Furthermore, comparison data between different types of 3D printed scaffolds for bone regeneration are presented. A discussion on Photo-responsive and magneto-responsive 3D printed scaffolds that have been fabricated for bone regeneration is included. Research concerning drug loaded scaffolds as well as incorporation of nanocarriers into scaffolds for bone regeneration is provided. Chemotherapy utilized in osteosarcoma therapy has severe adverse effects due to being non-selective between healthy cells and tumor cells. A possible way to overcome this is to utilize nanotechnology. Therefore, research detailing other types of nanocarriers that have the potential to be incorporated into 3D printed scaffolds for localized adjuvant therapy is presented.